2011
DOI: 10.1080/15235882.2011.625884
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Majoritarian Tales: Portraits of Bilingual Teachers Deconstructing Deficit Views of Bilingual Learners

Abstract: This article argues that teacher-education programs often promote surface conceptions of inclusivity that limit preservice teachers' ability to understand and build upon the lived experiences of culturally and linguistically diverse youth. Conventional wisdom implies that teachers of color are native informants of these lived experiences; however, teacher educators should create opportunities for all teacher candidates to challenge prevalent myths about communities of color. Using critical race theory (CRT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…However, there is more and more research showing that students' heritage language skills need to be utilized in the teaching of English (e.g., Cummins, 1991;Dorner et al, 2007;Fránquiz et al, 2011;Gándara & Orfield, 2012;Padilla, 2006). Further, there is a growing area of educational research examining the impact of bilingual youths' interpreting experiences on their social and academic development.…”
Section: Language Brokeringmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there is more and more research showing that students' heritage language skills need to be utilized in the teaching of English (e.g., Cummins, 1991;Dorner et al, 2007;Fránquiz et al, 2011;Gándara & Orfield, 2012;Padilla, 2006). Further, there is a growing area of educational research examining the impact of bilingual youths' interpreting experiences on their social and academic development.…”
Section: Language Brokeringmentioning
confidence: 95%
“…The fact that they did so through comparing language and literacy skills in both Spanish and English uniquely positions their talents as bilinguals in mainstream classroom settings (Fránquiz et al, 2011;Martínez, 2010). These different levels of awareness-noticing the general importance of language in their learning and making specific connections between interpreting and vocabulary development, for example-represent important aspects of the asset approach to bilingualism and linguistic diversity (Moll et al, 1992;Paris, 2010).…”
Section: Interpreting and Academic Successmentioning
confidence: 97%
“…(p. 4) Similarly, in a study of Latinas who struggled to negotiate their Latina teacher identity, Aguilar, MacGillivray, and Walker (2003) found that Latina teachers either silenced or distanced themselves or internalized the values and perspectives of the school and its teachers to navigate school discourse. Thus, it cannot be assumed that teachers of color are better prepared than White teachers to succeed in teaching students of color (Sheets, 2004;Fránquiz, Salazar, & DeNicolo, 2011). This article seeks to inform teacher educators of the identity struggles Latina teachers may experience while working with Latino students so that they encourage pre-service teachers of color to take a critical look at their own cultural knowledge and to be conscious of the capital they possess and embody as they enter the teaching profession.…”
Section: A Closer Look At Latina Teachersmentioning
confidence: 95%
“…Research on cognitive and academic functioning has shown the enhanced benefits of dual language education (Bialystok, 2007;Collier & Thomas, 2004;Lindholm-Leary & Block, 2010). Dual language promotes important social and cultural outcomes, such as healthy multi-generational cultural and linguistic communities while also presenting a counter narrative to dominant racial ideologies that disregard Latina/o culture (Fránquiz, Salazar, & DeNicolo, 2011;Wiemelt & Welton, 2015). Dual language education values diversity and fosters cultural acceptance; requires collaborative, flexible, and tailored professional development for educators and parents; welcomes and connects different communities; maintains high expectations for all students and views diversity as an asset; and develops curricula that is developmentally appropriate and attentive to context and culture (García, 2005;McLaughlin, 2013;Schachter & Gass, 2013).…”
Section: Emergent Bilinguals and Dual Language Educationmentioning
confidence: 99%